Pre‐registration: Why and How. Issue 1 (15th February 2021) - P. Simmons, Joseph; D. Nelson, Leif; Simonsohn, Uri
Abstract : In this article, we (1) discuss the reasons why pre‐registration is a good idea, both for the field and individual researchers, (2) respond to arguments against pre‐registration, (3) describe how to best write and review a pre‐registration, and (4) comment on pre‐registration's rapidly accelerating popularity. Along the way, we describe the (big) problem that pre‐registration can solve (i.e., false positives caused by p‐hacking), while also offering viable solutions to the problems that pre‐registration cannot solve (e.g., hidden confounds or fraud). Pre‐registration does not guarantee that every published finding will be true, but without it you can safely bet that many more will be false. It is time for our field to embrace pre‐registration, while taking steps to ensure that it is done right. Abstract : This article is part of a Research Dialogue: Krishna (2021): https://doi.org/10.1002/jcpy.1211 Pham & Oh (2021): https://doi.org/10.1002/jcpy.1209 Simmons et al. (2021): https://doi.org/10.1002/jcpy.1207 Pham & Oh (2021): https://doi.org/10.1002/jcpy.1213